Cross-cultural adaptation and psychometric properties of the Spanish Quality in Psychiatric Care Forensic Inpatient Staff (QPC-FIPS) instrument - Marta Domínguez del Campo; Antonio R. Moreno-Poyato; Montserrat Puig-Llobet; Maria Teresa Lluch-Canut; Nathalia Rodríguez Zunino; Manuel Tomás-Jiménez; Sara Sanchez-Balcells; Agneta Schröder; Lars-Olov Lundqvist; Gemma Escuder-Romeva; Juan Roldán-Merino (Scientific Reports, 2022)
Abstract "Quality in Psychiatric Care-Forensic Inpatient Staff (QPC-FIPS) is an instrument of Swedish origin validated to measure the perception of the quality of mental health care provided by forensic psychiatry professionals. The aim of this study was to cross-culturally adapt the QPC-FIPS instrument and to evaluate the psychometric properties of the Spanish version of the instrument. A psychometric study was carried out. For validity, content validity, convergent validity and construct validity were included. For reliability, the analysis of internal consistency and temporal stability was included. The sample consisted of 153 mental health professionals from four Forensic Psychiatry units. The adapted Spanish version of the QPC-FIPS scale was configured with the same number of items and dimensions as the original. The psychometric properties, in terms of temporal stability and internal consistency, were adequate and the factor structure, such as the homogeneity of the dimensions of the Spanish version of the QPC-FIPS, was equivalent to the original Swedish version. We found that the QPC_FIPS-Spanish is a valid, reliable and easy-to-apply instrument for assessing the self-perception of professionals regarding the care they provide.